Antidiscrimination Meets Integration Policies: Exploring New Diversity-Related Challenges in Europe - Magazzini, Tina (Social sciences (Basel), 2021)
Contemporary European societies are increasingly diverse. Migration both within and to Europe has contributed over the past decades to the rise of new religious, racial, ethnic, social, cultural and economic inequality. Such transformations have raised questions about the (multi-level) governance of diversity in Europe, thus determining new challenges for both scholars and policy-makers. Whilst the debate around diversity stemming from migration has become a major topic in urban studies, political science and sociology in Europe, Critical Race Studies and Intersectionality have become central in US approaches to understanding inequality and social injustice. Among the fields where ‘managing diversity’ has become particularly pressing, methodological issues on how to best approach minorities that suffer from multiple discrimination represent some of the hottest subjects of concern. Stemming from the interest in putting into dialogue the existing American scholarship on CRT and anti-discrimination with the European focus on migrant integration, this paper explores the issue of integration in relation to intersectionality by merging the two frames. In doing so, it provides some observations about the complementarity of a racial justice approach for facing the new diversity-related challenges in European polity. In particular, it illustrates how Critical Race Studies can contribute to the analysis of inequality in Europe while drawing on the integration literature.